Global Deletion of ALDH1A1 and ALDH1A2 Genes Does Not Affect Viability but Blocks Spermatogenesis - Topping, Traci; Griswold, Michael D. (Frontiers in Endocrinology, 2022)
The transition of undifferentiated A spermatogonia to differentiated spermatogonia requires the action of retinoic acid (RA). The synthesis of retinoic acid from retinal in the seminiferous epithelium is a result of the action of aldehyde dehydrogenases termed ALDH1A1, ALDH1A2, and ALDH1A3. We used a mouse with a global deletion of the Aldh1a1 gene that is phenotypically normal and the CRE-loxP approach to eliminate Aldh1a2 genes globally and from Sertoli cells and germ cells. The results show that global elimination of Aldh1a1 and Aldh1a2 genes blocks spermatogenesis but does not appear to affect viability. The cell specific elimination of Aldh1a2 gene showed that retinoic acid synthesis by Sertoli cells is required for the initial round of spermatogonial differentiation but that there is no requirement for retinoic acid synthesis by germ cells. In both the global gene deletion and the cell specific gene deletions the maintenance of Aldh1a3 activity could not compensate.